2023
DOI: 10.1007/s12144-023-04503-6
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to COVID-19 and aggression: the mediating role of anxiety and the moderating role of rumination

Abstract: The pandemic of COVID-19 is now posing a worldwide hazard to one’s health. Exposure to COVID-19 may cause negative emotions like anxiety, which is one of recognized risk factors for aggressive behaviors. This study looked into the effect of exposure to COVID-19 on aggression and how anxiety may act as a mediating factor, as well as lastly how rumination could moderate a variety of indirect paths during the epidemic of COVID-19. According to the current study’s findings, which included a sizable sample of Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Furthermore, Johnson et al suggested that exposure to different environments alters the genetic vulnerability of adolescents by influencing the expression of genetic factors [55]. In this regard, it is of interest that a significantly positive relationship between exposure to COVID-19 and an increased risk of stress has been detected and that this can lead to emotional/behavioral outcomes, such as anxiety, which might represent a mediating factor for aggressive behavior development [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Johnson et al suggested that exposure to different environments alters the genetic vulnerability of adolescents by influencing the expression of genetic factors [55]. In this regard, it is of interest that a significantly positive relationship between exposure to COVID-19 and an increased risk of stress has been detected and that this can lead to emotional/behavioral outcomes, such as anxiety, which might represent a mediating factor for aggressive behavior development [11].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is interesting to note that during the COVID-19 pandemic, a significant increase in ADHD cases was recorded. It is possible that COVID-19-related stressors triggered or aggravated cognitive, emotional, and physiological reactions that lead to impulsive-aggressive behavior [11].…”
Section: Factors Associated With Adhdmentioning
confidence: 99%
“…This intriguing observation suggests a potential indication of emerging aggressive behaviors before the diagnosis of COVID-19 or concerns surrounding the discharge process and the readjustment to daily life post-quarantine. The context of the SARS-CoV-2 pandemic highlights that exposure to COVID-19 may elicit negative emotions, such as anxiety, a recognized risk factor for aggressive behaviors [47,48]. COVID-19 itself can be associated with delirium [49,50], agitation, and symptoms of depression, anxiety, and insomnia, [51], together with obsessive-compulsive behaviors [52], which could exacerbate aggressive behavior; aggressiveness and violence themselves have been identified as possible manifestations of SARS-CoV-2-unmasked psychiatric conditions, such as, potentially, manic episodes [53,54] The joinpoint regression results show that joinpoints can be related to important moments.…”
Section: Discussionmentioning
confidence: 99%
“…Some prototypical externalizing problems include general disinhibition (e.g., ignoring rules, deadlines, or other's wishes), callous aggression (e.g., physical or emotional violence against others, fighting, or hurting people intentionally), and problematic alcohol use (White & Labouvie, 1989). Little research has examined changes among general disinhibition or callous aggression associated with the pandemic, although researchers have reported a rise in aggression following exposure to COVID-19 among Chinese college students (Hu et al, 2023), among American adults experiencing pandemic-related lockdowns (Killgore et al, 2021), and among Twitter users following lockdowns (Hsu & Tsai, 2022), which could be related to externalizing symptoms.…”
Section: Covid-19's Impact On Externalizing Problemsmentioning
confidence: 99%